Phase‐only transmit beampattern synthesis with sparse arrays via alternating optimisation‐alternating direction of the multipliers method - Li, Lifeng; Liu, Xingang; Wang, Xiangrong; Hu, Mengkai; Du, Yufeng (IET microwaves, antennas & propagation, 2024)
To get simultaneously sparse and constant modulus excitation to reduce the complexity of the array and the mutual effect of neighbouring elements, a novel algorithm via alternating optimisation‐alternating direction of the multipliers method is developed. This method uses the total transmitting power as the objective function to optimise the sparsity and the amplitude of excitation simultaneously. Numerical results are provided to verify its effectiveness. The authors propose a novel algorithm via alternating optimisation‐alternating direction of the multipliers method to get simultaneously sparse and constant modulus excitation to reduce the complexity of the array and the mutual effect of neighbouring elements.